2015
DOI: 10.1002/2015ja021575
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for lightning‐associated enhancement of the ionospheric sporadic E layer dependent on lightning stroke energy

Abstract: In this study we analyze the lightning data obtained by the World‐Wide Lightning Location Network (WWLLN) and hourly ionospheric data observed by ionosondes located at Sanya and Beijing, to examine the changes in ionospheric electron density in response to the underlying thunderstorms and to investigate the possible connection between lightning discharges and the enhancement of the ionospheric sporadic E(Es) layer. We identify a statistically significant enhancement and a decrease in altitude of the Es layer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Thus, the vertical ion convergence by itself is far from sufficient to explain the strong E s summer maximum. Some other physical processes should also be considered in the geographical distribution and spatial variations in E s layers which play 25 important roles in determining the global morphology of E s such as the magnetic field, ionospheric electric field, chemical processes of metallic ions, large geomagnetic storms, and meteorological processes in the lower atmosphere (e.g., Mathews, 1998;Carter and Forbes, 1999;Davis and Johnson, 2005;Johnson and Davis, 2006;Haldoupis, 2012;Yue et al, 2012;Feng et al, 2013;Yu et al, 2015) Haldoupis et al (2007) proposed the seasonal dependence of E s could be explained by the seasonal variation of the meteor 30 influx into the upper atmosphere. However, it has been largely accepted now that sporadic meteoroids provides a extremely greater meteor mass on average than meteor showers (Ceplecha et al, 1998;Baggaley, 2002;Janches et al, 2002;Williams and Murad, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the vertical ion convergence by itself is far from sufficient to explain the strong E s summer maximum. Some other physical processes should also be considered in the geographical distribution and spatial variations in E s layers which play 25 important roles in determining the global morphology of E s such as the magnetic field, ionospheric electric field, chemical processes of metallic ions, large geomagnetic storms, and meteorological processes in the lower atmosphere (e.g., Mathews, 1998;Carter and Forbes, 1999;Davis and Johnson, 2005;Johnson and Davis, 2006;Haldoupis, 2012;Yue et al, 2012;Feng et al, 2013;Yu et al, 2015) Haldoupis et al (2007) proposed the seasonal dependence of E s could be explained by the seasonal variation of the meteor 30 influx into the upper atmosphere. However, it has been largely accepted now that sporadic meteoroids provides a extremely greater meteor mass on average than meteor showers (Ceplecha et al, 1998;Baggaley, 2002;Janches et al, 2002;Williams and Murad, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Tropospheric thunderstorms are well known to disturb the lower ionosphere at altitudes ranging from 60 to 90 km, through lightning electric fields (Cheng et al, 2007;Davis & Lo, 2008;Lu, 2006;Mende et al, 2005;Pasko et al, 1997) and convective atmospheric gravity waves (GWs) (Lay & Shao, 2011;Sentman et al, 2003; 10.1002/2017GL074977 Taylor & Hapgood, 1988). It is also found that the ionospheric sporadic E (E s ) layer at ∼100 km can be influenced by lightning (Davis & Johnson, 2005;Yu et al, 2015). Before the term "sporadic E" was invented, the occurrence of the abnormal nocturnal E region at nearly 105 km was proposed to be correlated with thunderstorms on the basis of a few observed events (Ratcliffe & White, 1934;Watson-Watt, 1933).…”
Section: Introductionmentioning
confidence: 99%
“…There is no 6 or 30 hours time delay between the thunderstorm activity and the response of the Es like in the case of Davis and Johnson 2005. Response: Thanks for your comments. In the previous SEA studies ( Davis and Johnson, 2005;Johnson and Davis, 2006;Davis and Lo, 2008;Barta et al, 2013Barta et al, , 2015Yu et al, 2015;Yu et al, 2017), the hourly lightning data can hardly exhibit the development of thunderstorms at different stage. In this study, when using the averaged WWLLN stroke rate as an indicator of the intensity of thunderstorms, it seems that the foEs and Es occurrence rate increase with the development of thunderstorm activity, as shown in Figure 2.…”
Section: Interactive Commentmentioning
confidence: 89%
“…Changes: Please see page 2 lines 15-17. "After that, more studies applied the same methodology of SEA on lightning and Es layer measurements using the hourly lightning events as trigger times (Johnson and Davis, 2006;Davis and Lo, 2008;Barta et al, 2013Barta et al, , 2015Yu et al, 2015)." Please see page 2 lines 24-26.…”
Section: Interactive Commentmentioning
confidence: 99%